PORTAL OF UNIVERSITIES AND PROPOSAL FOR NEW MODULES EXPANSION - HORNYAK GREGANOVA, Radomira; TOTHOVA, Darina (Trends in education, 2015)
Portal of Universities was established on land of association EUNIS-SK in 2005 as a project Ministry of education, science, research and sport of the Slovak republic and solves since 2006. It forms a gate to information's for applicants of study, university students and the general public. It also creates a gate to national projects and other information systems, such as KEGA (projects of the Cultural and Educational Grant Agency of the Ministry of Education, Science, Research and Sport), CREPC (Central Register of Publication Activities), Electronisation of booking to university and more. Universities provide information about their faculties, study programs, they published events organized by their universities and e-courses via Portal VS. The paper deals with the current status of the Portal of Universities and possibilities of its expansion in the future.
Keywords: Portal of Universities; modules; current status; expansion.